Validitas Tes Keterampilan Berpikir Kritis Remaja (TKBKR) di Universitas Pendidikan Indonesia - Krisnanda, Veno D.; R. Marfu’i, Lucky Nindi (Pusat Asesmen dan Pembelajaran, 2019)
This study aims to examine the validity of tests of critical thinking skills in adolescents. Validity tested based on; 1) test content, 2) response process, and 3) internal structure. The constructs of Critical Thinking Skills are 23 questions with the correct answer wrong with the answer answers in the form of reasons supporting the correct wrong answers. The subjects in this study amounted to 304 students from six faculties, namely FPMIPA, FIP, FPOK, FPIPS, FPBS, and FPTK at the Indonesian University of Education. The results of the study showed that of the 36 questions there were only 23 questions that could be maintained because 13 questions that had fallen had poor validity and measurement of adolescent critical thinking skills. Based on the results of the validity test of proof of the contents of the language expert, critical thinking experts, and experts in analytical ability mathematically evaluate that this test is feasible to use and the constructed answer key is in accordance with the questions presented. Based on evidences of the internal structure, it is explained that the KMO value of the results of factor analysis shows the number 0.570 with 2 components formed, namely analysis and evaluation capabilities. Suggestions for further research, TKBK has not been tested in its external validity in depth so that there needs to be evidence based on the relationship to other variables and based on the consequences of the test.